History of osteochondral allograft transplantation. - Nikolaou, V S; Giannoudis, P V (Injury, 2017)
Osteochondral defects or injuries represent the most challenging entities to treat, especially when occur to young and active patients. For centuries, it has been recognized that such defects are almost impossible to treat. However, surgeons have never stopped the effort to develop reliable methods to restore articular cartilage and salvage the endangered joint function. Osteochondral allograft transplantation in human was first introduced by Eric Lexer in 1908. Since that era, several pioneers have been worked in the field of osteochondral allotransplantation, presenting and developing the basic research, the methodology and the surgical techniques. Herein we present in brief, the history and the early clinical results of osteochondral allograft transplantation in human.
Keywords: Allografts; Bone Transplantation; Cartilage, Articular; Graft Survival; History, 20th Century; Humans; Osteotomy; Outcome Assessment (Health Care); Transplantation, Homologous